Performance Analysis of Mesh Networking Implementation on Mikrotik Router Board 941 - Yudi Abdul Halim; Darwin Panjaitan; Alexander Silitonga; Suata Wan Kelispa Halawa; Roberto Kaban; Meiliyani Br Ginting (Karya Techno Solusindo, 2026)
The increasingly rapid development of computer network technology demands a network system that is reliable, flexible, and able to adapt to dynamic environmental conditions. One of the network technologies that is currently developing is mesh networking. Mesh networking is a network topology where each node can be connected to each other directly or indirectly through other nodes. This research aims to analyze the application of the mesh networking method using the Mikrotik RouterBoard 941 device. The research method used is experimental by configuring, implementing, and testing mesh networking on the Mikrotik RouterBoard 941. The results of the research show that mesh networking can be applied to the Mikrotik RouterBoard 941 by utilizing available features, such as OLSR (Optimized Link State Routing) and WDS (Wireless Distribution System). Mesh networking is able to increase redundancy and network availability, and can adapt to changes in network topology. However, mesh networking also has several disadvantages, such as configuration complexity, routing overhead, and the possibility of bottlenecks at certain nodes. REFERENCES Aisyah, A. (2022). Mesh Network Model On Internet Of Things (IoT) Systems For Environmental Monitoring. Ardhitya, A. I. (2021). Definition and Explanation of Microtics. Available at Http://Ilmukomputer. org/2013/01/04/Definition-and-Explanation-Mikrotik/. Accessed, 20. Arman, M., & Kasran, K. (2023). Wireless Network Analysis on IoT-Based ATM Machines at PT. Bank Negara Indonesia (Persero) Tbk KCP Watansoppeng. Scientific Journal of Information Systems and Informatics Engineering (JISTI), 6(1), 77–84. https://doi.org/10.57093/jisti.v6i1.151 Bahtiar, D., Febrianto, W. J., Maulana, A., Saputra, S., Darmawan, W., Tafonao, R. P., Julianto, R., Zai, R., & Djutalov, R. (2021). Basic Introduction to Computer Network InstallationUsing Mikrotik. Informatics Student Creativity, 2, 507–518. Fahmi Faizar, F. (2020). The effect of Bluetooth 5.0 interference on 802.11b network performance. 2(10), 1390–1399. Fahriani, N. (2024). From Wired to Wireless:(Evolution and Innovation of Modern Networks). Hariyanto, T., & Rahayu, M. (2021). The WiFi bandwidth system of ad-hoc networks uses the class-based queue method. JITEL (Scientific Journal of Telecommunications, Electronics, and Power Electricity), 1(1), 17–24. https://doi.org/10.35313/jitel.v1.i1.2021.17-24 Iqbal, M., & Tambunan, L. (2021). Designing samba servers using ubuntu servers and network configuration using mikrotik routerboards (case study of pt. Mesitechmitra purnabangun). JSR: Robotic Information Systems Network, 5(1), 1–8. Juniarti, T. S. J. (2025). Wireless Mesh Network Implementation Strategy for Wireless Network Improvement and Reliability. Journal of Software Engineering and Information Systems (SEIS), 98–107. Kurniasih, D., & Rusfiana, Y. (2021). Analytical Techniques. Nugroho, H. A. S. A., Hartati, S., & Sonhaji, S. (2023). Comparative analysis of OSPF and static routing protocols for the optimization of xyz high school computer networks. Transformation, 18(2), 1–11. https://doi.org/10.56357/jt.v18i2.310 Oktafiandi, H. (2021). Design and build a wireless mesh network using ad-hoc Optimized Link State Routing (OLSR). Journal of Economics and Informatics Engineering, 9(2), 70–75. Putra, F. P. E., Arissandi, D. E., Rofiqi, A., & Hidayat, M. F. (2025). The Utilization of Mikrotik in Bandwidth Management in School Networks. Journal of Informatics and Computer Technology, 5. Rahman, A., & Nurwarsito, H. (2020). Performance analysis of is-is routing protocol and eigrp routing protocol on mesh topology network. Journal of Information Technology and Computer Science Development, 4(11), 4139–4147. Siddik, M., Lubis, A. P., & Sahren, S. (2023). Optimizing Internet Network Speed in Mts Daarussalam Using the Simple Queue Method. Journal of Science and Social Research, 6(1), 117. https://doi.org/10.54314/jssr.v6i1.1179 Simanjuntak, E. (2021). Analysis of Students' Learning Difficulties in Mixed Calculation Operation Material in Grade IV of Sd Negeri 067246 Medan Academic Year 2020/2021. Siswanto, D. (2021). Implementation of Wireless Mesh Network on Local Area Network (LAN) Network. Journal of Science and Social Research, 4307(1), 20–27. Tarigan, I. S. B. (2020). Analysis of Students' Difficulties in Learning to Listen in Class V of Sdn 048232 Kabanjahe Academic Year 2019/2020. Toyib, R., Wijaya, A., & Apridiansyah, Y. (2024). The implementation of the Point to Point method uses Mikrotik Router Board Type RB411AH for internet network access. Decode: Journal of Information Technology Education, 4(1), 225–238. Yastianto, S. (2021). Design and build a VLAN network using the Routing Information Protocol (RIP) method using a Cisco router in the Department of Computer Engineering of the Police.